Exploring the photoexcited electron transfer dynamics in artificial sunscreen PBSA-coupled biocompatible ZnO quantum dots. (4th May 2022) - Mubeen, Muhammad; Khalid, Muhammad Adnan; Shahrum, Saba; Mukhtar, Maria; Sumreen, Poshmal; Tabassum, Mamoona; Ul-Hamid, Anwar; Nadeem, Muhammad Arif; Iqbal, Azhar
Abstract : Frequent exposure to ultraviolet (UV) radiation without any protection turns out to be a fatal threat leading to skin cancer, necessitating the use of sunscreen cosmetic product with enhanced efficiency to dissipate the UV absorbed energy. Abstract : Frequent exposure to ultraviolet (UV) radiation without any protection turns out to be a fatal threat leading to skin cancer. This can be forestalled by the direct application of sunscreen cosmetic products. The efficiency of UV absorbed energy dissipation by sunscreen can be enhanced if it contains a charge and/or energy acceptor species. 2-Phenylbenzimidazole-5-sulfonic acid (PBSA) is an artificial sunscreen component that acts as an electron donor in alliance with biocompatible and environment-friendly ZnO quantum dot (QD) acceptors. Functionalized ZnO QDs are synthesized by the colloidal method using mercaptoacetic acid (MAA), mercaptopropionic acid (MPA), l -cysteine (LC), ethylene glycol (EG), β-alanine (BA), and citric acid (CA) ligands that help to develop an interaction with the PBSA. Steady-state photoluminescence (SSPL) and time-resolved photoluminescence (TRPL) analysis were employed to study the efficiency and rate of the electron transfer (ET) process. Our findings reveal that the electron transfer rate strongly depends on the size and the nature of the functionalizing ligands. The highest ET efficiency for the PBSA-ZnO QD dyad is noticed in the case of MAA (87.9%) and the lowest with the CA (33.8%) ligand. This indicates that MAA-functionalized ZnO QDs are the best electron acceptor amongst the other aforementioned functionalizing ligands as evidenced by the cyclic voltammetry (CV) measurements of PBSA- and MAA-functionalized ZnO QDs. These findings suggest that in the case of the PBSA-ZnO QD dyad, small-sized thiol functionalizing ligands like MAA, MPA and LC facilitate the electron transfer process more than large-sized ligands containing hydroxyl and amine functionalities, such as EG, BA, and CA.